ON FRIENDSHIP: A DEFENSE OF A PLURALITY OF PERSPECTIVES - Pérez, Diana I. (Analysis. Journal of Philosophical Research, 2024)
This work presents some ideas about friendship, based on the TV series Sex and the City, which crudely exposes the social changes that have occurred in recent years in the field of interpersonal relationships. In the first section I clarify the notion of “personal point of view” and the various ways of accessing them. In the second I analyze the points of view present in this serie. I take this case to analyze the plurality of perspectives that characterize friendship amongst the four protagonists. I also explore other possible points of view that the series presents. Finally, I present my points of view as a spectator of this TV show; my objective is to reflect on the changes that have occurred in recent years in interpersonal relationships. The final balance provides decisive support for the promotion of respect for a plurality of perspectives a central for life in society.